Penggunaan Pembelajaran Problem Based Learning (PBL) untuk Mengurangi Miskonsepsi Siswa pada Materi Asam Basa - Dewi Yul Launde; Emma J Pongoh; Jeanne M Tuerah (Oxygenius Journal Of Chemistry Education, 2020)
This study aims to determine the effect of the use of Problem Based Learning towards reducing students' misconceptions on acid-base material. The learning model used in this study is the Problem Based Learning (PBL) learning model. The population in this study were all students of class XII IPA in Tomitas Caritas Catholic High School while the sample used was class XII IPA 2. Data collection techniques used a two-tier diagnostic test. Analysis of the data used in this study is the Rasch model and hypothesis testing. The results showed that there were still students who experienced misconceptions even including students who had high abilities, and the average pretest learning outcomes = 48.6 while the average posttest learning outcomes = 86.6. The results of the study for the hypothesis test were analyzed using the T-test statistic at a significant level of 0.05 and the results obtained were obtained at 7.90> 1.684 Ttable so that H0 was rejected and H1 was accepted. Based on these results it can be concluded that the use of Problem Based Learning learning models can reduce student misconceptionsThis study aims to determine the effect of the use of Problem Based Learning towards reducing students' misconceptions on acid-base material. The learning model used in this study is the Problem Based Learning (PBL) learning model. The population in this study were all students of class XII IPA in Tomitas Caritas Catholic High School while the sample used was class XII IPA 2. Data collection techniques used a two-tier diagnostic test. Analysis of the data used in this study is the Rasch model and hypothesis testing. The results showed that there were still students who experienced misconceptions even including students who had high abilities, and the average pretest learning outcomes = 48.6 while the average posttest learning outcomes = 86.6. The results of the study for the hypothesis test were analyzed using the T-test statistic at a significant level of 0.05 and the results obtained were obtained at 7.90> 1.684 Ttable so that H0 was rejected and H1 was accepted. Based on these results it can be concluded that the use of Problem Based Learning learning models can reduce student misconceptions